A descriptive analysis of prospective science teachers' beliefs and expectations about laboratory course - BAYRAM, HALE (ELSEVIER SCIENCE BV, 2010)
This study investigated prospective science teachers' beliefs and expectations about chemistry laboratory course at the beginning and the end of the semester. 27 freshmen participated in this study. They carried out 11 experiments and had a metacognitive training by filling reflective forms, which were developed by the authors, and making pre- and post-discussions throughout a semester. The participants were administered pre- and post-course reflective forms, before and after the treatment, respectively and filled pre- and post-performance forms, at the beginning and the end of each lesson, respectively. They prepared reports of each experiment and received feedback for both their performation during the lessons and their reports. At the end of each lesson the students were asked authentic research questions related to the topic of the experiment and sometimes asked to design a new experiment. Students' answers to the pre- and post-course reflective forms were analyzed and coded. The frequencies of these codes were presented and discussed. The analysis of pre- and post-course reflective forms showed that the diversity of the students' responses about laboratory course increased throughout the course period. The results also indicated the increase in the use of metacognitive skills and the outcome expectations, especially self-efficacy beliefs of prospective science teachers. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Prospective science teachers; metacognitive training; motivation; laboratory instruction